An investigation into pupil oracy with Year 10 pupils studying GCSE History in an all girls' school - Wagner, C (2015)
The promotion of pupil oracy is accepted as a key feature of an effective classroom. Pupil oracy has been shown to enhance learning in a wide variety of ways, notably at primary level. In addition, a potential link between the ways in which some girls speak at school and the way in which this could limit their progression in the workplace has been identified. However, there has been little research into girls’ oracy in single-sex secondary schools. Oracy in History teaching has also been somewhat neglected. This study examined which teaching strategies might encourage girls’ oracy in History lessons and which factors appear to prevent girls from participating actively in History lessons. The question of whether the encouragement of girls’ oracy in History lessons can improve cognition and confidence was also investigated. Case studies, semi-structured interviews with pupils and teachers, pupil observations and teaching interventions were utilised in the investigation. Findings suggested that learning activities such as the use of role-play and whole class discussion based around historical controversies can successfully promote girls’ oracy. It was also found that there is a range of factors that can prevent girls from participating actively in History lessons, such as a lack of confidence in girls’ understanding and knowledge of the topics being studied and pupils being given insufficient time to prepare for discussions. The role of confidence to speak in front of peers and the impact of social relationships between girls in the classroom also emerged as highly significant. It was concluded from this small-scale study that the encouragement of girls’ oracy in History lessons can improve girls’ cognition and confidence. This can be done by providing girls with repeated opportunities to discuss controversial topics in whole class settings.